Effect of insulin during oocyte maturation in vitro on bovine early embryo development : partially evaluated by novel fluorescent staining - Lindgren, Ida (SLU/Dept. of Clinical Sciences (until 231231), 2014)
Fertility is of central interest in the dairy production but has during the last decades declined. Increased milk yield has resulted in high pressure on the metabolism of the dairy cows that are supposed to manage the transition from dry cows to lactating cows within a few weeks around the parturition. Much indicate that metabolism and fertility are closely linked, with insulin playing a substantial part. There are many studies suggesting that the main part of gestation loss can be found during the early embryo development, a period which can be studied in vitro. The aim of this study was to test the effect of insulin during maturation in vitro and to evaluate two different fluorescent stainings on oocytes and embryos; a nuclear stain and a staining of apoptotic cells through the terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL)-method. Bovine cumulus-oocyte-complexes (n=991) were aspirated from abattoir-derived ovaries. The oocytes were matured in vitro under different insulin-conditions (Z: 0 μg/ml L: 0.1 μg/ml H: 10 μg/ml). After maturation, oocytes were either removed for staining or fertilized and cultured in vitro to day eight after fertilization. All blastocysts were morphologically assessed at day seven and eight. Cumulus-oocyte-complexes removed before fertilization and day eight blastocysts were later stained with TUNEL- and nuclear stain for evaluation. Statistical analysis was executed on arc sinus squareroot transformed values. The effect of treatments were analysed by ANOVA. 132 matured oocytes and 230 day eight blastocysts from eight batches were analysed. There was no significant difference between the treatments regarding oocytes cleaved 44h post fertilization (Z:0.85±0.02 L: 0.85±0.02 H: 0.89±0.03, p>0.05). Insulin tended to impair the fraction of blastocysts developed on day seven from cleaved oocytes (Z: 0.22±0.02 L: 0.17±0.02 H: 0.14±0.02, p=0.05). There was a tendency for insulin treated groups to have more of the earlier development stages and also less blastocysts of high quality grades when morphologically assessed at day eight compared to control group. The difference was significant when comparing treated groups together versus the control group (p<0.05). There was no significant difference in apoptotic cells in the blastocysts (Z: 0.021±0.003 L: 0.026±0.003 H: 0.028±0.003) nor in apoptotic cells in the outer two layers of the cumulus-complexes (Z: 0.052±0.025 L: 0.039±0.016 H: 0.077±0.044). In this study, insulin during oocyte maturation in vitro impaired the blastocyst development both regarding fraction, stage and grade at day seven and eight. The TUNEL-kit evaluated did not work satisfactory for staining of embryos and cumulus-oocyte-complexes with multiple cell-layers. The nuclear staining tested however, seem to be a good candidate for staining of blastocysts and cumulus-oocyte-complexes with a limited amount of cell-layers. The stain is easy to use and further did not bleach after several weeks of storage.